1988
DOI: 10.1007/bf00213845
|View full text |Cite
|
Sign up to set email alerts
|

Retinal projections in sockeye salmon smolts (Oncorhynchus nerka)

Abstract: The retinal projections in 2-year-old salmon smolt (Oncorhynchus nerka) are significantly different from those observed in other teleosts examined to date in that the projections are more extensive. Very noticeable are extensive projections to most of the dorsal thalamus, to all layers of the optic tectum, and into the periaqueductal gray of the torus semicircularis. The salmon smolt has bilateral retinal projections to the diencephalon and pretectum. A small retinal projection to the lateral habenular nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Cells of the suprachiasmatic nucleus were labeled after DiI application to most telencephalic regions (Vv, Vd, Vs, Dm, DdϩDl-d, Dc, Dp; see above, and Folgueira et al, 2004a). The retinal targets observed in the diencephalon and optic tectum were similar to those reported in the rainbow trout (Pinganaud and Clairambault, 1979) and in Oncorhynchus nerka (Shiga et al, 1987;Ebbesson et al, 1988) and will not be described here.…”
Section: Telencephalic Regions Of Origin Of Some Extratelencephalic Pmentioning
confidence: 62%
“…Cells of the suprachiasmatic nucleus were labeled after DiI application to most telencephalic regions (Vv, Vd, Vs, Dm, DdϩDl-d, Dc, Dp; see above, and Folgueira et al, 2004a). The retinal targets observed in the diencephalon and optic tectum were similar to those reported in the rainbow trout (Pinganaud and Clairambault, 1979) and in Oncorhynchus nerka (Shiga et al, 1987;Ebbesson et al, 1988) and will not be described here.…”
Section: Telencephalic Regions Of Origin Of Some Extratelencephalic Pmentioning
confidence: 62%
“…We found a few uncrossed direct telencephalic projections in the present study. Ebbesson et al [1988] reported contralateral direct projections to the caudal telencephalon in sockeye salmon smolts. Since relatively more widespread projections are seen in the salmon smolt [Ebbesson et al, 1988] and no such projections were reported in adult salmons, these projections may be transient during ontogeny, although Repérant et al [1982] did not report such projections in juvenile specimens of Acipenser güldenstädti (15-30 cm long).…”
Section: Discussionmentioning
confidence: 99%
“…Ebbesson et al [1988] reported contralateral direct projections to the caudal telencephalon in sockeye salmon smolts. Since relatively more widespread projections are seen in the salmon smolt [Ebbesson et al, 1988] and no such projections were reported in adult salmons, these projections may be transient during ontogeny, although Repérant et al [1982] did not report such projections in juvenile specimens of Acipenser güldenstädti (15-30 cm long). Nevertheless the specimens of Acipenser transmontanus (65-70 cm long) used in the present study were mature, and therefore adults of this species may retain primitive features of the visual system, including direct telencephalic projections and bilateral retinal projections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It varies from one (Campbell and Ebbesson 1969;Anders and Hibbard 1974;Rep&ant and Lemire 1976;Rep6rant etal. 1976;Lemire and Rep&ant 1976;Voneida and Sligar 1976;Peyrichoux et al 1977;Springer and Landreth 1977;Pinganaud and Clairambault 1979;Ebbesson and Ito 1980;Ebbesson and O'Donnell 1980;Meyer and Ebbesson 1981;Fernald 1982;Prasada Rao and Sharma 1982;Ito et al 1984;Fraley and Sharma 1984;Lfizfi( et al 1984;Bazer and Ebbesson 1987;Ebbesson et al 1988;Rajendra Babu and Prasada Rao 1988;Wilm and Fritzsch 1990;Wullimann et al 1991), two (Ebbesson 1968Sharma 1972;Vanegas and Ebbesson 1973;Sas and Maler 1986;Lfiz/tr et al 1987; Von Bartheld and Meyer 1988), three (Ekstr6m 1982(Ekstr6m , 1984Collin 1989), five (Springer and Gaffney 1981;Springer and Mednick 1985), six Butler and Saidel 1991), to ten ).…”
Section: Hypothalamusmentioning
confidence: 99%